(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2016)
This paper describes a method for creating a spectacular brilliant light flash with a high current, low voltage pulse discharge through a hydrated salt and metal mix. Photography of flashes generated are presented and analysed for consistency with the hydrino theory of R. Mills (2011). Photography shows generation of a high density of photons away from the electrodes consistent with a secondary photon generating reaction mechanism.